FORMATION THE PROFESSIONAL COMPETENCE OF MARKETING MANAGER IN THE AREAS OF INFORMATION TECHNOLOGY - Мозгова, Г. В. (Bulletin of V. N. Karazin Kharkiv National University Economic Series, 2013)
Grounded the model of professional competence of marketing managers in the areas of information technologies: established skills with modern information technology, the analysis shows that modern information technology is proposed structural logic circuit forming the professional competence of marketing managers in the field of information technology.